The national landscape of unplanned 30‐day readmissions after total laryngectomy. (20th November 2017) - Ferrandino, Rocco; Garneau, Jonathan; Roof, Scott; Pacheco, Caitlin; Poojary, Priti; Saha, Aparna; Chauhan, Kinsuk; Miles, Brett
Abstract : Objectives/Hypothesis: Examine rates of readmission after total laryngectomy and determine primary etiologies, timing, and risk factors for unplanned readmission. Study Design: Retrospective cohort study. Methods: The Nationwide Readmissions Database was queried for patients who underwent total laryngectomy between January 2013 and November 2013. Patient‐, procedure‐, admission‐, and institution‐level characteristics were compared for patients with and without unplanned 30‐day readmission. Outcomes of interest included rates, etiology, and timing of readmission. Multivariate logistic regression was used to identify predictors of 30‐day readmission. Results: There were 2, 931 total laryngectomies performed in 2013 with an unplanned readmission rate of 17.5%. Postoperative fistula accounted for 13.7% of readmissions. The odds of readmission were elevated for patients undergoing concurrent procedures, including primary tracheoesophageal fistulization (adjusted odds ratio [aOR]: 2.44, 95% confidence interval [CI]: 1.15‐5.18, P = .02) and/or pedicle graft or flap procedures (aOR: 1.73, 95% CI: 1.13‐2.66, P = .01). Additionally, patients with comorbid coagulopathy (aOR: 3.04, 95% CI: 1.13‐8.22, P = .03), liver disease (aOR: 2.48, 95% CI: 1.08‐5.71, P = .03), and valvular heart disease (aOR: 3.18, 95% CI: 1.20‐8.41, P = .02) had increased risk for unplanned 30‐day readmission. Private insurance and longer lengths of stay were associated with decreased odds of readmission. Conclusions: Nearly one‐fifth of total laryngectomy patients are readmitted to the hospital within 30 days of discharge. Risk factors identified in this nationally representative cohort should be carefully considered during the postoperative period to reduce preventable readmissions after total laryngectomy. Level of Evidence: 2c Laryngoscope, 1842–1850, 2018